Effect of pH and buffer on substrate binding and catalysis by cis-aconitate decarboxylase - Mingming Zhao; Chutao Chen; Wulf Blankenfeldt; Frank Pessler; Konrad Büssow (Scientific Reports)
Abstract cis-Aconitate decarboxylase (ACOD1, CAD, IRG1) catalyses the synthesis of itaconic acid in activated myeloid cells such as macrophages. Several histidine residues in the active site bind the substrate and enable the decarboxylation reaction. The in vitro activity of ACOD1 enzymes is commonly determined by incubation with substrate, followed by HPLC measurement of itaconic acid production. Phosphate buffers have often been used for this assay. However, the influence of buffer type on enzyme activity has not been investigated. Here, the effect of buffer and pH on enzyme kinetics of human and mouse ACOD1 and Aspergillus terreus CAD was investigated. It was found that high concentrations of phosphate inhibit the three enzymes. An alternative buffer was selected and the assay was adapted to the 96-well microtitre plate format for increased throughput. Enzyme kinetics were determined in the pH range of 5.5–8.25. A strong increase of K M values was observed between the physiologically relevant pH values 7.5 and 8.25. The data indicate that more than one histidine residue needs to be protonated in the active site for binding the substrate.